The Role of Micro Waqf Bank through Joint Liability Qard Financing in MSME Empowerment - Hadi, Solikhul; Raunaqa, Yoga (MALIA: Journal of Islamic Banking and Finance, 2022)
This study aims to describe: (1) how the implementation of the practice in empowering MSMEs at the Assa Berkah Sejahtera Kudus Micro Waqf Bank, (2) how the results of qardh financing and the results of the practice of joint responsibility financing in empowering MSMEs by the Assa Berkah Sejahtera Kudus Micro Waqf Bank, and (3) the inhibiting factors for financing the practice of joint responsibility at the Assa Berkah Sejahtera Kudus Micro Waqf Bank and what are the solutions to overcome these inhibiting factors. This research is a type of field research (field research). The approach used by researchers in this study is qualitative research. Sources of data in this study are primary data and secondary data. Primary data sources are managers, as well as several customers of the Assa Berkah Sejahtera Micro Waqf Bank. Meanwhile, secondary data sources are library books and documentation. Based on the results of the research obtained, this study shows that: (1) The implementation of the practice of joint responsibility is going well using a qardh contract and has succeeded in being a solution for customers who have difficulty paying the installments for the repayment of business capital. (2) The results of qardh financing are an increase in business and an increase in income, while the results of the practice of joint responsibility for empowering MSMEs are creating a sense of kinship and responsibility among members (3) The inhibiting factor is the lack of concern and a sense of responsibility with several prospective customers who are still selfish alone. The solution to overcome the inhibiting factors is to hold mandatory group training for five consecutive days with one of the materials, namely the practice of joint responsibility financing.